Monster eyeballs - Wilson, Jacqueline; Lewis, Stephen, 1971- (London : Egmont, 2002)
Kate likes nearly everything about school except for her big, bullying classmate Mark, but when their brothers Robbie and Andrew become friends, Mark ends up at Kate's house for Robbie's birthday party during which Kate learns some very useful information.
1.6
K-3.
K-3
Keywords: Brothers and sisters -- Juvenile fiction; Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Brothers and sisters -- Fiction; Bullies -- Fiction; Schools -- Fiction; Bullies -- Fiction; School stories; Siblings -- Fiction; Readers (Elementary).